Schema theory: Critical review and implications for the role of cognition in a new theory of motor learning - Sherwood, D. E.; Lee, T. D. (Research Quarterly for Exercise and Sport, 2003)
This paper is based on a symposium celebrating the 26th anniversary of the publication of "A Schema Theory of Discrete Motor Skill Learning" (Schmidt, 1975) held at the annual conference of the North American Society for the Psychology of Sport and Physical Activity in June 2001. We provide a brief historical context for schema theory and a review of the development of the mechanistic approach to motor learning in general. We explore recent findings in mental practice, observational learning, augmented feedback presentation, and the variability of practice that are inconsistent with schema theory and provide a rationale for the importance of cognitive activity in motor learning.